Garra hexagonarostris, a new labeonine fish (Teleostei: Cyprinidae) from the Chindwin basin, Manipur, Northeast India, and a critical review on the taxonomic status of G. minimus, G. alticaputus, G. nigricauda, G. kimini, and G. tyao - Nebeshwar, Kongbrailatpam; Rameshori, Yumnam; Prabina, Salam (Zootaxa, 2024)
Garra hexagonarostris, a new member of the ‘proboscis species group’, is described from the Chakpi River of Chindwin basin in Manipur, India. The new species is distinguished by the following combination of characters: a prominent hexagon-shaped unilobed proboscis with five large-sized conical tubercles on anterior margin, and three or four medium-sized conical tubercles on anteroventral region; transverse lobe with 13−35 small- to medium-sized conical tubercles; lateral surface of snout swollen with 8−18 small- to medium-sized conical tubercles; 31−32 lateral-line scales including three pored scales on caudal fin; and a large arch-shaped black spot on each side of opercle, immediately anterior to upper angle of gill opening. The taxonomic status of several species of Garra from Arunachal Pradesh and Mizoram, is reviewed and accordingly Garra minimus is considered as a junior synonym of G. quadratirostris; G. nigricauda as a junior synonym of G. arunachalensis; G. alticaputus and G. kimini as junior synonyms of G. birostris; and G. tyao as a junior synonym of G. rakhinica.